T-cell invigoration to tumour burden ratio associated with anti-PD-1 response - Huang, Alexander C.; Postow, Michael A.; Orlowski, Robert J.; Mick, Rosemarie; Bengsch, Bertram; Manne, Sasikanth; Xu, Wei; Harmon, Shannon; Giles, Josephine R.; Wenz, Brandon; Adamow, Matthew; Kuk, Deborah; et al. (Nature (London), 2017)
Despite the success of monotherapies based on blockade of programmed cell death 1 (PD-1) in human melanoma, most patients do not experience durable clinical benefit. Pre-existing T-cell infiltration and/or the presence of PD-L1 in tumours may be used as indicators of clinical response; however, blood-based profiling to understand the mechanisms of PD-1 blockade has not been widely explored. Here we use immune profiling of peripheral blood from patients with stage IV melanoma before and after treatment with the PD-1-targeting antibody pembrolizumab and identify pharmacodynamic changes in circulating exhausted-phenotype CD8 T cells (T ex cells). Most of the patients demonstrated an immunological response to pembrolizumab. Clinical failure in many patients was not solely due to an inability to induce immune reinvigoration, but rather resulted from an imbalance between T-cell reinvigoration and tumour burden. The magnitude of reinvigoration of circulating T ex cells determined in relation to pretreatment tumour burden correlated with clinical response. By focused profiling of a mechanistically relevant circulating T-cell subpopulation calibrated to pretreatment disease burden, we identify a clinically accessible potential on-treatment predictor of response to PD-1 blockade. The clinical benefit of anti-PD-1 antibody treatment is dependent on the extent to which exhausted CD8 T cells are reinvigorated in relation to the tumour burden of the patient. Blood biomarkers of blockade therapy response Only a small proportion of patients with advanced melanoma currently experience a long-term clinical benefit from therapeutic PD-1 blockade. Until now, blood-based profiling has not been widely explored as a means to understand the mechanisms of PD-1 blockade. In this study, Alexander Huang et al . analyse CD8 T cells in the blood and show that the clinical benefit of PD-1 blockade depends on the extent to which it reinvigorates exhausted CD8 T cells in relation to the pre-treatment tumour burden. Identifying the ratio of tumour burden to CD8 T-cell reinvigoration may help to predict how well a patient will respond to PD-1-blocking therapy.